Alkaline Electrochemical Reduction of a Magnesium Ferrospinel into Metallic Iron for the Valorisation of Magnetite-Based Metallurgical Waste. Issue 7 (23rd July 2021) - Lopes, Daniela V.; Lisenkov, Aleksey D.; Sergiienko, Sergii A.; Constantinescu, Gabriel; Sarabando, Artur; Quina, Margarida J.; Frade, Jorge R.; Kovalevsky, Andrei V.
Abstract : The electrochemical reduction of iron oxides in alkaline media arises as a novel approach for ironmaking and iron-rich waste valorisation. Strong advantages and attractive aspects of alkaline electroreduction include lower electric energy consumption, absence of CO2 emissions, and non-polluting valuable by-products such as H2 and O2 . Another potential advantage originates from the compatibility of this concept with intermittent renewable energies. However, to bring this technology to a competitive level, especially compared to the traditional steelmaking, innovative approaches and developments in materials processing and their appropriate integration into the electrolysis process are required. This research work explores the prospects for electrochemical reduction of a magnesium-containing ferrospinel, as a potential component in iron-containing wastes. The experimental approach considers bulk cathode- and suspension-based electrolysis concepts, which allow reaching 55% and 20% Faradaic efficiencies of the reduction to metallic iron, respectively. The effects imposed by the magnesium presence on the electroreduction kinetics, phase composition and morphology of the electroreduction products are evaluated and discussed. The obtained results open new perspectives for the recovery of metallurgical residues with low magnesium impurities content.